Cavum Septum Pellucidum Epidermoid- An Extremely rare occurrence - Srinivas, Dwarakanath; Chalikwar, Raghavendra; Mahadevan, Anita; Somanna, Sampath (Nepal Journal of Neuroscience, 2018)
Supratentorialintraventricularepidermoids are very rare and midline septal pellucidal epidermoids are even more uncommon with only one case being reported in available literature. A 42-year-old lady with no previous complaints was admitted to the emergency services with history of intermittent headache, vomiting and giddiness of 3 months duration. A cranial computed tomography (CT) revealed a hypodense, non-enhancing intraventricular mass lesion and cranial magnetic resonance imaging (MRI) demonstrated a non-enhancing mass lesion in the septum pellucidum suggestive of an epidermoid. She underwent endoscopic-assisted surgery via an interhemispheric transcallosal approach. Intra-operatively, the lesion was located in the enlarged cavum septum pellucidum and was removed totally. An extensive literature review unearthed only 10 cases of intraventricular epidermoids and one in the septum pellucidum. We present only the second case of a midline septum pellucidum epidermoid and reflect on the paucity of supratentorial intraventricular midline epidermoids. Nepal Journal of Neuroscience 15:32-34, 2018